Women's and Health Workers' Voices in Open, Inclusive Communities and Effective Spaces (VOICES): Measuring Governance Outcomes in Reproductive and Maternal Health Programmes. (12th January 2017) - Sebert Kuhlmann, Anne K.; Gullo, Sara; Galavotti, Christine; Grant, Carolyn; Cavatore, Maria; Posnock, Samuel
Abstract : Given the growing popularity of the social accountability approach to governance, we developed and tested measures of governance outcomes to evaluate maternal and reproductive health social accountability interventions. We articulate a theory of change for how CARE's Community Score Card ©, a social accountability approach, 1) empowers women, 2) empowers health workers and 3) creates expanded, inclusive and effective spaces for the two to interact. Our measures worked well in surveys of women and health workers. For women, eight of 13 scales had alphas ≥.70. For health workers, five of 11 scales were ≥.70; four were .60–.69. To our knowledge, this is the first attempt to develop comprehensive measures of governance outcomes to evaluate a social accountability approach for maternal and reproductive health.